2022
DOI: 10.1029/2022jc018843
|View full text |Cite
|
Sign up to set email alerts
|

Intraseasonal Variability of Surface Circulation in the Indo‐Pacific Warm Pool Induced by Summer Monsoon Intraseasonal Oscillations

Abstract: The Indian summer monsoon intraseasonal oscillation (MISO) is the most influential mode of tropical atmospheric intraseasonal variability in boreal summer (May–October). This study investigates how the MISO drives the intraseasonal variability (ISV) of zonal currents (U) in the Indo‐Pacific warm pool (IPWP) region. An analysis of satellite observations confirms a close association between U ISV and the MISO, with MISO‐induced surface U anomalies reaching 16–19 cm s−1 near the equator and 4–5 cm s−1 in the Nort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 88 publications
0
2
0
Order By: Relevance
“…The influx of freshwater from precipitation, Yangtze River discharge, and strength of the Taiwan Current, lead to a decrease in SSS to below normal levels during BSISO phases 5 to 7 (Figures 3e-3h, Column E). Although, we have not explicitly investigated all the sources of freshwater influx in this region, apart from precipitation, we mention them in consideration of the major current systems and northward movement of the active BSISO ( (Song et al, 2022). Kim et al (2014) suggested that 80% of the total freshwater in the East China Sea and its neighboring region originates from Changjiang River discharge.…”
Section: Impact Of Bsiso On Changes In the Sst And Sss In The Necs An...mentioning
confidence: 99%
“…The influx of freshwater from precipitation, Yangtze River discharge, and strength of the Taiwan Current, lead to a decrease in SSS to below normal levels during BSISO phases 5 to 7 (Figures 3e-3h, Column E). Although, we have not explicitly investigated all the sources of freshwater influx in this region, apart from precipitation, we mention them in consideration of the major current systems and northward movement of the active BSISO ( (Song et al, 2022). Kim et al (2014) suggested that 80% of the total freshwater in the East China Sea and its neighboring region originates from Changjiang River discharge.…”
Section: Impact Of Bsiso On Changes In the Sst And Sss In The Necs An...mentioning
confidence: 99%
“…However, in the Pacific region, limited in situ observations have resulted in few systematic studies on the seasonal spatiotemporal distribution of ocean circulation ISVs. Atmospheric ISOs, which exhibit significant seasonal characteristics (Lee et al 2013), strongly influence the upper ocean (Song et al 2019(Song et al , 2022. Besides the external forcing by atmospheric ISOs, ocean internal variability also plays a significant role in surface current ISVs in the western Pacific.…”
Section: Introductionmentioning
confidence: 99%